Application Of Cooperative Learning Model Type Of Numbered Head Together To Increase Activity And Learning Outcome Of Students Of Class VIII SMP Negeri 1 Praya Barat Daya - M. Agus Satriawan; Syahrir; Puji Lestari (LPPM Institut Studi Islam Sunan Doe, 2022)
The low understanding of the students in mastering the material was cuased by teacher’s method used conventional method and less attention with another method. So that way, it needed an interative learning approach to solve the problems aspecially in prism and pyramid. The learning approach that mean here is Numbered Head Together. The research aimed to increase students’ activities and achievement of SMPN 1 Praya Barat Daya in academic years 2020/2021 by implementing Numbered Head Together learning model. The research used classroom action research with two cycles. Each cycles consist of planning, acting, observing and reflecting. The subject of the research was students VIII 3 class with total subject 23 students. Based on the data analysis was gotten that there were increasing students activities and achhievement from first cycle to the second cycle with average score 2,77 in active categories with classical completeness 82,60% and average score 78,04. And the cycle to average score was 3,05 with medium categories and the percetage 91.30% with average 83,91. Therefore, it took conclusion that the implementation of Numbered Head Together Learning Model can increase students’ activities and achievement of SMPN 1 Praya Barat Daya in academic years 2020/2021.